(untitled) (Journal of Health Sciences, 2013)
Introduction: Preterm delivery is the delivery before 37 weeks of gestation are completed. Preterm birth is a major course of neonatal morbidity and mortality, the incidence of premature delivery in developedcountries is 5 to 9%. Aims of this study were to determine the common etiological factors for preterm delivery, most common weeks of gestation for pretern delivery, and most commom way of delivery for preterm delivery.Methods: The study included 600 patients divided into two groups, experimental group (included 300 preterm delivered pregnant women), control group (included 300 term delivered women).Results: The incidence of preterm delivery in pregnant women younger than 18 years was 4.4%, and in pregnant women older than 35 years was 14%. 44.6 % of preterm delivered women at the experimentalgroup had lower education. In the experimental group burdened obstetrical history had 29%, 17.2% had a preterm delivery, 35.6% had a premature rupture of membranes, 15% had a preterm delivery before32 weeks of gestation, 12.4% between 32-33.6 weeks of gestation, while 72.6% of deliveries were between 34- 36.6 weeks of gestation. Multiple pregnancy as an etiological factor was present in 10.07% ofcases. Extragenital diseases were present in 10.4%. In the experimental group there were 29%, while in the control group there were 15% subjects with burdened obstetrical history.Conclusions: Preterm birth more often occurs in a pregnant women younger than 18 and older than 35 years, and in a pregnant women of lower educational degree. Preterm delivery in the most commoncases was fi nished in period from 34 to 36.6 weeks of gestation. The most common etiological factor of preterm delivery in the experimental group was preterm rupture of membranes and idiopathic pretermdelivery.